EFFECT OF HYDROGEL PROVISION OF SHED AND PRP COMBINANTION ON OSTEOCLAST DECREASING IN THE ALVEOLAR BONE OF MALE WISTAR RAT (IN VIVO) - Hidayat, Rahmat; Muhtar, Muhamat; Pangestu, Mualif Dayu (Odonto : Dental Journal, 2021)
ABSTRACTBackground: The process of orthodontic bone resorption and remodelling occur simultaneously. Areas under continuous stress experience nutritional deficiencies and hypoxia, which results in cell death and cause alveolar bone resorption. The increase in osteoclasts is associated with the inflammatory process because it is accompanied by an increase in inflammatory mediators. The combination of SHED and PRP can induce regeneration of the alveolar bone of teeth and can inhibit the bone resorption process thereby suppressing the inflammatory process.Method: This research method was experimental post-test only control group design, with a total sample of 32 individuals treated with PRP gel, SHED gel, a combination of PRP and SHED, and povidone iodine with a duration of 14 days. Wedge application to the interdental teeth to produce the effect of orthodontic movement. Analysis of the one way ANOVA hypothesis test found that there was a significant difference in the reduction of osteoclasts in each experimental group (P <0.05).Result: It can be concluded that the mean osteoclast reduction in the PRP group was 359±107.3, SHED 392±170.5, the combination of PRP and SHED 480±151.3, povidone iodine 480±151.3.Conclusion: There is an effect of the combination of SHED and PRP on the reduction of osteoclasts in the alveolar bone of male Wistar rat.